Disability hate speech social, cultural and political contexts - Sherry, Mark 1966-; Olsen, Terje; Vedeler, Janikke Solstad; Eriksen, John (Interdisciplinary disability studies, 2019)
"This book, the first to specifically focus on disability hate speech, explains what disability hate speech is, why it is important, what laws regulate it (both online and in person) and how it is different from other forms of hate. Unfortunately, disability is often ignored or overlooked in academic, legal, political and cultural analyses of the broader problem of hate speech. Its unique personal, ideological, economic, political and legal dimensions have not been recognized - until now. Disability hate speech is an everyday experience for many people, leaving terrible psycho-emotional scars. This book includes personal testimonies from victims discussing the personal impact of disability hate speech, explaining in detail how such hatred affects them. It also presents legal, historical, psychological, and cultural analyses, including the results of the first surveys and in-depth interviews ever conducted on this topic in some countries. This book makes a vital contribution to understanding disability hatred and prejudice, and will be of particular interest to those studying issues associated with hate speech, disability, psychology, law, and prejudice"--